Systems, methods, and apparatus for cryogenic refrigeration - Black R. C. Randall C.; Hilton J. P. Jeremy P.; Rose G. Geordie; Petroff J. C. Jacob Craig; Uchaykin S. V. Sergey Victorovich
Title screen